INVENTARISASI BUNYI BAHASA KUI DI PULAU ALOR NUSA TENGGARA TIMUR (Widyadari : Jurnal Pendidikan, 2020)
The study of sound inventory of Kui language in Alor Island was very important. The sound involved vowel and consonant. The sound inventories were done by three steps namely 1) Complementary Distribution, 2) Minimal Pair, and 3) Similar Pair. Based on the study of Complementary Distributions found that Kui language has vowel sounds namely [a], [i], [u], [e], and [o], in open tribes. The sounds of [Ʌ], [I], [U], [O], and [E] were found in closed tribes. Consonant sounds namely: [b], [m], [p], [f], [t], [l], [r], [g], and [h] were fully distributed, there were at the initial position, middle, or end of words. The consonant sounds [d], [n], [s], [k], [w], and [y] were distributed at the initial and middle position of words, while the consonant [j] was distributed at the middle position of word. Minimum pairs of vowel phonemic relationships were found / i / - / o /, / e / - / a /, / i / - / e /, / i / - / e /, and / u / - / o /. The totals were 22 vocabulary words. Similar pairs were found vocal phonemes / a / - / e /; / i / - / u /; / i / - / u /; / a / - / i /; / i / - / u /; / o / - / a /; / i / - / e /; / o / - / i /; / e / - / i /; / u / - / i /; and / a / - / u / and consonant phonemes / l / - / t /; / m / - / h /; / r / - / p /; / w / - / r /; / b / - / m /; / p / - / n /; / k / - / d /; / t / - / d /; / m / - / w /; / d / - / s /; / k / - / t /; / k / - / l /; and / n / - / p /. The total were 24 vocabularies.